2014
DOI: 10.1021/jm500916t
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (R)-1-(7-Chloro-2,2-bis(fluoromethyl)chroman-4-yl)-3-(3-methylisoquinolin-5-yl)urea (A-1165442): A Temperature-Neutral Transient Receptor Potential Vanilloid-1 (TRPV1) Antagonist with Analgesic Efficacy

Abstract: The synthesis and characterization of a series of selective, orally bioavailable 1-(chroman-4-yl)urea TRPV1 antagonists is described. Whereas first-generation antagonists that inhibit all modes of TRPV1 activation can elicit hyperthermia, the compounds disclosed herein do not elevate core body temperature in preclinical models and only partially block acid activation of TRPV1. Advancing the SAR of this series led to the eventual identification of (R)-1-(7-chloro-2,2-bis(fluoromethyl)chroman-4-yl)-3-(3-methylis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 53 publications
(89 reference statements)
1
31
0
Order By: Relevance
“…These data encouraged a more focused investigation of SAR to optimization of the chromanyl urea series, concluding in the discovery of R ‐1‐(7‐chloro‐2,2‐bis(fluoromethyl)chroman‐4‐yl)‐3‐(3‐methylisoquinolin‐5‐yl)‐urea 28 (A‐1165442; Fig. ), a TRPV1 antagonist with good analgesic effect, temperature‐neutral profile, favorable pharmacokinetic behavior, and significant efficacy against osteoarthritic pain in rodents (hTRPV1 IC 50 = 9 nM in Ca 2+ influx assay) …”
Section: Medicinal Chemistry Of Trpv1 Antagonistsmentioning
confidence: 99%
“…These data encouraged a more focused investigation of SAR to optimization of the chromanyl urea series, concluding in the discovery of R ‐1‐(7‐chloro‐2,2‐bis(fluoromethyl)chroman‐4‐yl)‐3‐(3‐methylisoquinolin‐5‐yl)‐urea 28 (A‐1165442; Fig. ), a TRPV1 antagonist with good analgesic effect, temperature‐neutral profile, favorable pharmacokinetic behavior, and significant efficacy against osteoarthritic pain in rodents (hTRPV1 IC 50 = 9 nM in Ca 2+ influx assay) …”
Section: Medicinal Chemistry Of Trpv1 Antagonistsmentioning
confidence: 99%
“…With a second generation of TRPV1 antagonists under development that demonstrate analgesic effects in the MIA model and are devoid of the on-target-mediated side effects of hyperthermia [77] and burn risk, the clinical evaluation of TRPV1 antagonists can now progress unhampered.…”
Section: Resultsmentioning
confidence: 99%
“…The blockade of heat or capsaicin activation of TRPV1 does not make a significant contribution, whereas the potency of TRPV1 antagonists to induce hyperthermia relates most closely to their potency to block proton-induced activation of TRPV1. This information has been exploited in the development of a second-generation TRPV1 antagonists without the side effects of burn risk and hyperthermia [76,77]. For instance, AMG8562 an antagonist that potentiates TRPV1 activation by protons through positive allosteric modulation does not cause hyperthermia in rodents [78]; however, there is a requirement for a 46-fold higher plasma concentration for comparable efficacy when compared with AM8163 a compound that blocks all modalities of activation [78].…”
Section: Adverse Effects Of Trpv1 Antagonismmentioning
confidence: 99%
“…Fortunately, several compounds have been found that differentially affect the channel. For instance, some block capsaicin, but not heat activation, suggesting that it could be feasible to separate the analgesic effects of TRPV1 antagonists from harmful side effects (Lehto and others 2008) Indeed, second generation antagonists such as AMG8562, APHC1, APHC3 and A-1165442, 52 have already been tested for several inflammatory conditions with success in pain reduction while avoiding hyperthermia (Lehto and others 2008; Reilly and others 2012; Andreev and others 2013; Voight and others 2014). …”
Section: Trpv1mentioning
confidence: 99%